2005
DOI: 10.1007/s00213-005-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic enhancement of episodic memory in healthy young adults

Abstract: Given this specific drug effect and the well-known relevance of the hippocampal region for episodic memory, we conclude that this region appears to be the major target of cholinergic enhancement in healthy subjects due to long-term inhibition of AchE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 58 publications
(57 reference statements)
1
40
0
2
Order By: Relevance
“…A modest degree of memory enhancement is possible with the ADHD medications just mentioned as well as with medications developed for the treatment of Alzheimer's disease such as Aricept (donepezil), which raise levels of acetylcholine in the brain 8 . Several other compounds with different pharmacological actions are in early clinical trials, having shown positive effects on memory in healthy research subjects (see, for example, ref.…”
Section: Paths To Enhancementmentioning
confidence: 99%
“…A modest degree of memory enhancement is possible with the ADHD medications just mentioned as well as with medications developed for the treatment of Alzheimer's disease such as Aricept (donepezil), which raise levels of acetylcholine in the brain 8 . Several other compounds with different pharmacological actions are in early clinical trials, having shown positive effects on memory in healthy research subjects (see, for example, ref.…”
Section: Paths To Enhancementmentioning
confidence: 99%
“…Physicians who consider prescribing medication for neuroenhancement are disadvantaged by the dearth of valid clinical studies concerning the effects and safety of these drugs on normal persons. [9][10][11][12][13] Whether the effects shown in these studies can be extrapolated to the general population is unknown.…”
Section: Regulatory Ethical and Legal Issues To Consider Before Prementioning
confidence: 99%
“…Evidence suggests that these medications can improve memory and executive function in normal individuals. [9][10][11] However, other evidence suggests that these effects are complex, may not be uniformly positive across all dose levels or age groups, and do not enhance all aspects of executive function or memory. 12,13 While medications currently prescribed for neuroenhancement were developed to treat patients with disease, it is conceivable that medications will be developed and approved explicitly for improving cognition and memory in normal persons.…”
mentioning
confidence: 99%
“…Donepezil has also been shown to have nootropic effects after chronic use in healthy young (Grön et al, 2005) and elderly volunteers (FitzGerald et al, 2008). Studies such as these, however, shed little light on the role of acetylcholine on cognition because the status of the cholinergic system in these populations is altered by age, pathologies (Grön et al, 2005), and/or chronic use (Poirier, 2002). For this purpose, it is therefore ideal to administer single doses to healthy young adults in whom the cholinergic system is intact.…”
Section: Introductionmentioning
confidence: 97%